Critical Foundations of Social Work in Portugal and the Crisis of Capital - Lewgoy, Alzira Maria Baptista; Santos, Claudia Onica dos; Maciel, Fabricia Cristina de Astro [UNESP]; Coelho, Kathiuscia Aparecida Freitas Pereira; Morais-Tome, Maria Rosa Ferreira Clemente (Univ Caldas, 2025)
This article presents preliminary results of the research Historical and theoretical foundations of Social Service in Portugal: antecedents, memory and contemporary challenges, a subproject of the larger research entitled Social Service in History: Social Issues and Social Movements - Latin America and Europe (1960-2020 ). With the aim of expanding and deepening knowledge about the critical foundations of Social Work, we seek to identify trends in Social Work, answering the question if and how the critical aspect presents itself in Portugal?. This is documentary research, using as its source Curricular Unit Sheets (FUC) of the Study Plans of the 17 degrees. It is evident that in the FUC of Portuguese Social Service degrees there are no elements that indicate the Marxist critical aspect, currently.
Keywords: Capital Crisis; Social Service; Critical Fundamentals; Professional Training in Portugal